Job Stress, Work Life Balance, and Workplace Wellbeing : A Bibliometric Analysis - Kurnia Arumdani; Madziatul Churiyah (Jurnal Syntax Transformation, 2022)
The level of welfare, work stress and work-life balance, and employee psychology need to be considered for each individual. Individual welfare is expected to be an alternative for employees who have burdens both internally and externally. The application of workplace well being in the organization will be optimal for employee performance. The purpose of this study is to provide an extensive bibliometric literature study on workplace well-being. Articles quoted from the Scopus database, from 416 articles found from 2017 to 2021, there were 175 articles analyzed in the study. After managing the database, the researchers performed classification and visualization using VOSviewer software to be able to analyze co-authorship, co-occurrence, and citations. Overall, this literature study provides more references for further research on job stress, job life balance and workplace wellbeing at the level of education and seminars